Influence of ceramic thermal barrier coating on diesel engine performance using scum oil biodiesel at different compression ratios - Krishnamurthy K. N.; B. N. Akash Deep; Venkatesh Birur Jayanna; C. P. Sumalatha; Anwar Khan; Sarfaraz Kamangar; Saiful Islam; Abdul Razak; Yohanis Dabesa Jelila (Scientific Reports)
Abstract The present work explores the synergistic impact of mullite-based thermal barrier coatings (TBCs) and varying compression ratios (CRs) on the performance, combustion, and emission behavior of a single-cylinder, four-stroke variable compression ratio (VCR) diesel engine operated with Scum Oil Methyl Ester (SOME) diesel fuel blends. Mullite ceramic (3Al2O3·2SiO2) was applied via plasma spraying onto engine components including the piston crown, cylinder head, and intake/exhaust valves to minimize thermal losses. Experimental tests were carried out at CRs of 16.0, 17.5, and 19.0 using conventional diesel and blends of SOME (B20, B40, B60, B80, and B100 samples) in both coated and uncoated engine setups. The coated engine exhibited its best performance at CR 19, recording a BTE improvement of 7.51% for diesel and 5.75% for B20, alongside BSFC reductions of 14.28% and 9.09%, respectively, compared to the uncoated configuration. Additional enhancements were observed in terms of peak in-cylinder pressure, heat release rate, combustion efficiency, and reduced ignition delay and combustion duration. Emission measurements showed notable decreases in CO, HC, and smoke11.41%, 10.56%, and 9.43% for B20, and 6.16%, 7.10%, and 8.84% for diesel while only slight increases in NOx and CO2 emissions were recorded. These findings highlight the effectiveness of combining biodiesel and thermal barrier coatings in achieving improved efficiency and lower emissions, with the B20 blend at CR 19 showing the most favorable results for sustainable diesel engine operation.